Penetapan kadar flavonoid total ekstrak kayu raru (Cotylelobium lanceolatum Craib) berdasarkan perbedaan konsentrasi etanol dengan metode spektrofotometri Uv-Vis - Elma Natasya; Anny Sartika Daulay; Ridwanto Ridwanto; Yayuk Putri Rahayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The utilization of traditional medicinal plants for healing is the oldest form of medicine in the world. One of the plants that have many benefits and contain secondary metabolite compounds is raru bark (Cotylelobium lanceolatum Craib), used as a traditional medicine for diseases such as malaria, diarrhea, and diabetes. This study aims to determine what groups of compounds are contained in raru bark extract and the value of total flavonoid levels contained in raru bark extract in differences in ethanol concentrations (96%, 70%, 50%). The stages of this research include processing plant materials, making ethanol extracts of raru bark extract, characterization examination, phytochemical screening, and determining the total flavonoid content of raru bark ethanol extract. The section of raru bark was made by maceration method using 96%, 70%, and 50% ethanol. Then, the extract obtained was concentrated with a rotary evaporator, and the determination of total flavonoid content was carried out based on differences in ethanol concentration using the UV-Vis spectrophotometric method. The results showed that the ethanol extract of raru bark contained alkaloids, flavonoids, saponins, tannins, and steroid compounds. Determination of total flavonoid content by determining the maximum wavelength of quinine and calculating entire flavonoid content by UV-Vis spectrophotometric method. The results of the decision of complete flavonoid content of raru bark ethanol extract at 96% concentration are 1.9915 ± 0.0139 mg QE/g, 70% is 1.12492 ± 0.01532 mg QE/g, and for 50% is 0.95197 ± 0.01516 mg QE/g. So, the best ethanol concentration to produce flavonoid levels is 96%, which is higher than other ethanol concentrations.